2012
DOI: 10.5402/2012/958412
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of Photoluminescence in Porous Silicon Prepared by Metal-Assisted Chemical Etching

Abstract: Photoluminescent (PL) porous layers were formed on p-type silicon by a metal-assisted chemical etching method using H 2 O 2 as an oxidizing agent. Silver particles were deposited on the (100) Si surface prior to immersion in a solution of HF and H 2 O 2 . The morphology of the porous silicon (PS) layer formed by this method was investigated by atomic force microscopy (AFM). Depending on the metal-assisted chemical etching conditions, the macro-or microporous structures could be formed. Luminescence from metal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Using the wet Ag-ACE, Iatsunskyi et al reported that the PL spectrum of PS can be deconvoluted into three peaks located at 480, 550, and 670 nm (corresponding energies 2.58, 2.25, and 1.85 eV) [ 26 ]. They attributed the red PL peak (1.85 eV peak) to the QCE within the small Si NCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the wet Ag-ACE, Iatsunskyi et al reported that the PL spectrum of PS can be deconvoluted into three peaks located at 480, 550, and 670 nm (corresponding energies 2.58, 2.25, and 1.85 eV) [ 26 ]. They attributed the red PL peak (1.85 eV peak) to the QCE within the small Si NCs.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the oxygen-related peaks supports our suggestion about the PL origin of the first and third peaks which is related to the relaxation of the hole at the interface states related to Si-O bonds above the valence band, or the capture of an electron at the interface states near the conduction band edge and to the oxygen vacancies in SiO x on the surface of the Si NCs, respectively. In addition, the absence of any absorption peak below 700 cm −1 , usually attributed to the presence of metal bonds, excludes the hypothesis of Iatsunskyi et al suggesting that the green PL peak is associated with the formation of AgF or AgF 2 [ 26 ]. Figure 6 ii shows the appearance of the SiH x bonds in the stretching mode and localized between 2050 and 2200 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Changes in electrical and optical properties of the porous silicon under gas adsorptions are well-known and it is still under attentive investigation [4][5][6][7][8]. Porous silicon exhibits a great potential in optical sensor applications due to the possibility to change its reflectance index and luminescence properties after adsorption of molecules.…”
Section: Introductionmentioning
confidence: 99%